Isolation and establishment of Eimeria tenella populations from local broiler chicken farms - Loo, Shu-San; Mazlan Mohamed,; Farah Shafawati Mohd-Taib,; Khoo, Choon-Kiat; Wan, Kiew-Lian (Penerbit Universiti Kebangsaan Malaysia, 2022)
Coccidiosis is a major intestinal disease in the chicken production industry that is caused by one or more of the seven Eimeria species known to infect chickens. Development of effective diagnostic methods and controls requires comprehensive knowledge on the Eimeria species in the local population, particularly the pathogenic E. tenella. In this study, 35 faecal samples were collected from local chicken farms, and through microscopic observation, nine samples (26%) were found to contain Eimeria oocysts. Subsequently, two positive samples, namely NSN6 and SGR6, were selected and propagated via passage in coccidian-free chickens. Species identification analyses based on oocyst morphological characterisation suggested the presence of small-sized oocysts (E. acervulina and/or E. mitis) and medium-sized oocysts (E. necatrix, E. tenella, and/or E. praecox) in NSN6 while in SGR6, the large-sized oocysts (E. brunetti and/or E. maxima) were also present in addition to the small and medium-sized oocysts. Subsequently, species identification with PCR using species-specific primers was successful in determining the presence of specific Eimeria species, which are E. acervulina and E. tenella in NSN6, and E. acervulina, E. tenella, and E. maxima in SGR6. The E. tenella populations of NSN6 and SGR6, namely EtNSN6 and EtSGR6, respectively, were established via passage in coccidian-free chickens and oocyst recovery from the caeca. The purity of EtNSN6 and EtSGR6 populations were confirmed based on oocyst morphological characterisation and PCR. The established EtNSN6 and EtSGR6 populations would be useful as research models for local strains in the development of more effective control methods.